2022
DOI: 10.1101/2022.10.31.22281753
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis of gestational duration and spontaneous preterm birth identifies new maternal risk loci

Abstract: BackgroundPreterm birth (<37 weeks of gestation) is a major cause of neonatal death and morbidity. Up to 40% of the variation in timing of birth results from genetic factors, mostly due to the maternal genome.MethodsWe conducted a genome-wide meta-analysis of gestational duration and spontaneous preterm birth in 68,732 and 98,371 European mothers, respectively.ResultsWe detected 19 associated loci of which seven were novel. The loci mapped to several biologically plausible genes, includingHAND2whose express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Two large maternal GWASs of pregnancy duration have been conducted recently [38,39]. Both studies analysed the samples in two statistical models: case-control tests with preterm delivery as the outcome, and regression models of continuous gestational duration.…”
Section: Gwas Of Preterm Birth and Gestational Agementioning
confidence: 99%
See 3 more Smart Citations
“…Two large maternal GWASs of pregnancy duration have been conducted recently [38,39]. Both studies analysed the samples in two statistical models: case-control tests with preterm delivery as the outcome, and regression models of continuous gestational duration.…”
Section: Gwas Of Preterm Birth and Gestational Agementioning
confidence: 99%
“…In Solé-Navais et al [38], 23 genes were reported for GA, and 7 for PTD, of which all but 1 were also reported for GA. The Pasanen et al [39] study reported 15 genes for GA and 4 for PTD (of these 2 unique to PTD). Some samples were used in both studies, and the top hits were largely shared, but 14 of the genes were still unique to [38] and 7 unique to [39].…”
Section: Gwas Of Preterm Birth and Gestational Agementioning
confidence: 99%
See 2 more Smart Citations